(untitled) - Phạm, Thị Phương Dung (Cần Thơ, 2009)
This thesis was implemented aiming at finding out favored learning and teaching styles of English learners and teachers at Mekong University; teachers awareness of their learners learning styles and their own teaching styles; learners awareness of their learning styles; difference between learning styles of male and female learners and whether there was a mismatch between learning styles and teaching styles.
Keywords: English language,English teachers,English learners; Study and teaching,Training of,Studying of